EFEKTIFITAS KEBERLAKUAN PERATURAN DAERAH NOMOR 13 TAHUN 2002 TENTANG LARANGAN MENDIRIKAN TEMPAT USAHA MENPERBAIKI KENDARAAN BERMOTOR MENGGUNAKAN BADAN JALAN,TROTOAR DAN ATAS PARIT DI KOTA SAMARINDA - Waherson Sagala (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Sidewalks are part of highway engineering, with the aim of dividing the path between pedestrians and motor vehicle users. Given the pavement functions as a special path for pedestrians to use. Most bodies, sidewalks and upper trenches in Samarinda City have switched functions to other activities filled with permanent and non-permanent small buildings, such as kiosk stalls, street vendors, parking lots and businesses repairing motor vehicles using roads , sidewalks and above the trenches.Based on the results of research the authors get the fact that the enforcement of Regional Regulation No. 13 of 2002 on the prohibition of establishing a motor vehicle repair business on the roads, sidewalks and over the trenches in the city of Samarinda not run effectively hai because the content material regulation is still less clear about the criteria of place of business in addition, legal sanctions, both fines and confinement, are less burdensome to the people who use the roads, sidewalks and over ditches so as not to cause deterrent effects to the violating community. And the absence of legal sanctions for law enforcement officers who do not carry out their respective duties.Factors influencing the enforcement of Regional Regulation Number 13 Year 2002 regarding the prohibition to establish a place of vehicle repair business on the road, sidewalk and top of the trench in Samarinda city that is the factor of law enforcement officers, community factors and the substance of Local Regulation No. 13 of 2013 that there is still law enforcement who are less responsible for his work in the field and the lack of public awareness of local regulations especially Samarinda. Based on field research on Local Regulation No. 13 of 2002 the results of interviews with the Police Officers of Pamong Praja Samarinda City can be concluded that the lack of public awareness and lack of socialization of Local Government against Regional Regulation No. 13 of 2002. The factors causing ineffectiveness of the implementation of the law is the main factor of society is very influential in law enforcement. But the fact that the roads, sidewalks and the top of the trenches used as a place of business that is the land for a living or the necessities of life and the community also does not have other land to be used as their place of business.